Investigation of WENO schemes for 3D unstructured grids - Wieteska, Robert; Majewski, Jerzy; Rokicki, Jacek (Computer Assisted Methods in Engineering and Science, 2007)
This paper paper discusses accuracy of WENO reconstruction used for unstructured grids and applied to two common discretization approaches within Finite Volume Method (FVM). They are Cell Centered and Vertex Centered methods. The numerical results are shown for 3D supersonic flow in a channel and for ONERA M6 wing. The comparison of computational performance of both methods is included.